PROFITABILITY, FIRM VALUE, INCOME SMOOTHING: THE MODERATING ROLE OF FIRM GROWTH - Welly Chandra; Amrie Firmansyah; Estralita Trisnawati (Kesatuan Press, 2023)
This study examines the effect of profitability and firm value on income smoothing. In addition, this study examines the moderate effect of firm growth on the relationship between these variables. This study employs a sample of companies in the banking sector listed on the IDX. The number of samples in this study is 31 observations based on purposive sampling. Moreover, the hypothesis in this study was examined with multiple regression analysis for cross-section data. The results of this study suggest that profitability and firm value are not associated with income smoothing. Furthermore, firm growth cannot strengthen the negative relationship between profitability and income smoothing. Also, firm growth cannot strengthen the negative relationship between firm value and income smoothing.